(untitled) (Fiep Bulletin - online, 2012)
With the regulation of the profession of Physical Education in 1998 began in all Brazilian states the implementation of the Regional Councils of Physical Education (CREF3/SC). In Santa Catarina was created CREF3-SC in 1999 with a record of 2,000 (Two thousand) professionals. This article’s main objective is to record the history of the deployment CREF3/SC and specifically highlight the actions of the ethics committee of the board. Such registration is required by the understanding that many historical facts relevant to a particular job category get lost or lack of data in the literature. To realize these objectives it was decided to carry out a desk research (OLIVEIRA, 2007). In conclusion it is recorded that these 12 (Twelve) years after the implementation of Physical Education CREF3/SC Catarinense had greater representation in society and government.